Workshop Penyusunan Soal HOTS : Upaya Meningkatkan Kompetensi Pendidik di MI Islamiyah Palangka Raya - Sufiyatun Sufiyatun (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The workshop on the preparation of Higher Order Thinking Skills (HOTS) questions at MI Islamiyah Palangka Raya aims to improve the competence of educators in designing problems that challenge students’ high-level thinking skills. This study uses a qualitative descriptive method with a participatory approach, which involves interactive lectures, group discussions, hands-on practice in the preparation of questions, and integration of learning technologies. The results of the activity showed that participants gained a better understanding of the concept of HOTS, active learning strategies, and problem preparation techniques that can develop students’ critical, creative, and analytical thinking skills. Practice sessions involving the creation of questions and presentation of the results provide an opportunity for teachers to share experiences and constructive feedback. In addition, the introduction of educational applications and digital media opens up new insights into the importance of technology in supporting the learning process. Despite the challenges in mastering technology, the enthusiasm of the participants to implement technology in their learning was very high. In conclusion, this workshop makes a positive contribution to improving the professional competence of teachers, and to ensure the sustainability of the workshop results, follow-up is needed in the form of further training and support from the school.